P161 The impact of biologic therapies on Extra-Intestinal Manifestations in Inflammatory Bowel Disease: a multicentre observational study. (27th May 2021) - Ferretti, F; Monico, M C; Cannatelli, R; Lenti, M V; Di Sabatino, A; Carmagnola, S; Conforti, F; Pastorelli, L; Caprioli, F; Bezzio, C; Saibeni, S; Mazza, S; et al.
Abstract: Background: A high proportion of Inflammatory Bowel Disease (IBD) patients will develop extraintestinal manifestations (EIMs). Choosing the most appropriate therapeutic strategy among currently available biologics for each patient may often be challenging. Data regarding the effects of gut-selective therapies such as vedolizumab (VDZ) on new-onset and pre-existing EIMs are scarce and often discordant. The main aims of this study were to assess the cumulative incidence of new-onset EIMs and the course of pre-existing EIMs in a large cohort of IBD patients treated with VDZ compared to non-gut selective biologic agents. Methods: This multicenter retrospective study collected data of IBD patients on biologic therapy in clinical follow-up at 6 tertiary referral IBD units in Lombardy. Clinical and demographic data of IBD patients were collected. We calculated the cumulative incidence of new-onset EIMs since the introduction of the ongoing biologic therapy, comparing patients on VDZ with patients on non-gut selective therapies. Furthermore, we analyzed the course of pre-existing and new-onset EIMs in these two cohorts of patients. Results: Data about 973 IBD patients (624 CD, 339 UC, 10 IBD-U; median age 46 years; 59% males) on biologic therapy were collected. Of them, 215 were on VDZ and 758 were on non-gut-selective agents, with a median treatment duration with the ongoing therapy of 3 years. The overall prevalence of EIMs in this IBD cohort of patients was 19.8% (193/973 patients). The overall cumulative incidence of new-onset EIMs was of 4.1 % (40/973): 13 on VDZ (13/215) versus 27 (27/758) in the non-gut selective group (6% vs 3.6%, p = 0.1). Regardless of the type of biologic agents, the female sex and the duration of the ongoing biologic treatment were statistically associated with a higher risk of developing EIMs. About 17% of IBD patients reported a pre-existing EIM. Compared to non-gut selective therapies, patients on VDZ showed a significantly higher rate of worsening or absence of response (8.1% vs 19.4%, 12/148 vs 7/36, p=0.04). However, in both groups, a modification of the therapeutic protocol has been necessary with the introduction of adjunctive therapy, the switch, or the optimisation of the ongoing biologic therapy (27.8% patients on VDZ versus 25% on non-gut selective therapies, p=0.7). Conclusion: Our study suggests that the type of biologic treatment does not affect the risk of new-onset of EIMs. However, in the case of pre-existing EIMs, a subtle higher risk of worsening can be speculated after starting VDZ, even if the proportion of patients who will need adjunctive therapy, the optimisation or switch of the ongoing treatment would be similar between gut-selective and non-gut selective therapies.